2022
DOI: 10.1177/17411432221111659
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of female headteachers of boys’ senior high schools in Ghana

Abstract: This study examines the experiences of the only three female headteachers leading boys’ senior high schools (SHS) in Ghana to understand the uniqueness of their career journeys, on-the-job experiences and the leadership strategies. Qualitative phenomenological approach was used for the study. The three women were interviewed multiple times over a period of five months between November 2020 and March 2021. The data were inductively and deductively analysed to identify themes that help to tell their story. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…136,137,138 In Ghana, household phone surveys revealed that the wealthiest families were nearly ten times more likely to have hired private tutors than the poorest families. 139 In Senegal, increases in private tutoring were also concentrated among the richest households. 140 Additionally, parents took initiative to seek out additional educational resources for their child.…”
Section: Households' Ability and Preparedness To Weather The Shock Va...mentioning
confidence: 99%
“…136,137,138 In Ghana, household phone surveys revealed that the wealthiest families were nearly ten times more likely to have hired private tutors than the poorest families. 139 In Senegal, increases in private tutoring were also concentrated among the richest households. 140 Additionally, parents took initiative to seek out additional educational resources for their child.…”
Section: Households' Ability and Preparedness To Weather The Shock Va...mentioning
confidence: 99%